Neuromusic Education in Cognition and Quality-of-Life Promotion. An Outline - Gkintoni, Evgenia; Farmakopoulou, Ignatia; Theodoratou, Maria (Technium Social Sciences Journal, 2023)
The new cognitive field of neuromusical education and research combines neuroscience and music. This article reviews recent research literature and discusses the application of neuroscience to music education, highlighting the positive effects of music education on the cognitive functions of the brain and the enhancement of an individual’s quality of life. Consequently, the purpose of this study was to examine the value of music education in enhancing brain function and promoting quality of life, as well as its continued application in the contemporary educational environment.